A new stalk-eyed species of Batrachophthalmum Hendel (Diptera, Richardiidae) from Colombia - de Carvalho, Claudio J. B.; Wolff, Marta; Wendt, Lisiane D. (Zootaxa, 2011)
Batrachophthalmum quimbaya Carvalho, Wolff & Wendt, new species, from Santuario de Flora y Fauna Otún-Quimbaya, Colombia, is described. This stalk-eyed species of Richardiidae was collected at Bosque Sub-Andino in the central mountain range of Colombia. An identification key for two species of the genus, and for stalk-eyed species of the related genera Richardia Robineau-Desvoidy and Megalothoraca Hendel, are also added.